PERAN TENAGA PENDIDIK DAN ORANG TUA PADA ANAK BERDIAGNOSA ADHD - Hidayah, Dhea Ranafairuz Nurfikrishifa; Salsabila, Mutiara Chaella; Meilana, Septi Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Inclusive education is an approach that provides equal learning opportunities for all children, regardless of their background or abilities, including those with Attention Deficit Hyperactivity Disorder (ADHD). Teachers play a vital role in supporting the learning needs of children with ADHD by implementing specific strategies, such as providing additional attention, utilizing cognitive-behavioral approaches, and tailoring teaching methods to meet the child’s needs. This study aims to identify teachers' perspectives on inclusive education, their understanding of ADHD, and the strategies used in teaching and classroom management. Furthermore, it explores the challenges faced by teachers and the solutions they implement to support inclusive education. The findings reveal that collaboration between teachers, parents, and schools, along with specialized training for teachers, is critical to the success of teaching children with ADHD. Recommendations, such as the provision of shadow teachers, task adjustments, and additional facilities, can further enhance the effectiveness of inclusive education.